Labour Worry and Postpartum Discomfort of Primiparous Mothers in Konya, Turkey - Çankaya, Seyhan; Yilmaz, Sema Dereli (Africa Journal of Nursing and Midwifery, 2020)
Increased levels of worry about childbirth labour may lead to the development of obstetric complications. Therefore, this study was designed to determine the factors that affect the birth worry of primiparae. The population of the study consisted of the primiparous women between May and August 2018 in the Dr Ali Kemal Belviranl? Maternity and Children’s Hospital in the province of Konya, Turkey. A total of 240 primiparous women were selected by means of convenience sampling for this descriptive research. The Postpartum Comfort Questionnaire (PPCQ), the Oxford Worries about Labour Scale (OWLS), and a questionnaire that examines socio-demographic and obstetrical features were used to collect the data. The data were analysed with independent samples, the t-test, the one-way ANOVA, and Pearson’s correlation. The mean age of the women was 27.09 ± 5.04 (min.: 18, max.: 41) years and the mean gestation was 38.8 ± 1.1 weeks. The mean score of labour worry was higher while the mean score of postpartum comfort was lower for those women who had a caesarean delivery (OWLS: t = ?6.47, p = 0.001; PPCQ: t = 4.40, p = 0.001), who had high concerns or fears about labour or delivery (OWLS: t = ?7.05, p = 0.001; PPCQ: t = ?7.04, p = 0.001), who were not emotionally supported by their family during pregnancy (OWLS: t = 13.12, p = 0.001, PPCQ: t = 13.12, p = 0.001), and who had experiences of health problems during delivery (OWLS: t = ?5.01, p = 0.001; PPCQ: t = ?6.06, p = 0.001). It has been found that as the OWLS scores increase, the PPCQ scores also increase reflecting a positive correlation (r = 0.672, p < 0.001) between these variables. This study supports existing literature which states that factors such as health status, aspects of labour and social support affect labour worry and the postpartum comfort level. For this reason, increasing women’s comfort in the postpartum period may be provided by being informed about their physical and psychological health as of the antenatal period, and by giving midwifery care and health education that aim to determine their labour worry level and to eliminate it.